New Treatment Approaches for Hypertension and Diabetes - Alexander, Lori (MD Conference Express, 2012)
Hypertension is present in more than two-thirds of patients with type 2 diabetes and its development can precede and predict the development of hyperglycemia, while impaired glucose tolerance can predict the development of hypertension. This article presents an overview of the comorbidity problems associated with hypertension and diabetes.